2006
DOI: 10.1029/2006gl027798
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of electric field fluctuations associated with the aurora during northward IMF

Abstract: [1] We present a statistical study of scaling features of the electric field fluctuations measured by the DE2 satellite in the polar region during positive Bz IMF when the thetaaurora was observed by the DE1 satellite. It is demonstrated that the power spectra of the fluctuations have a power-law form at spatial scales from $0.5 km (the limit of resolution) to several thousands of kilometers, with a break near 100 km. The scaling properties of the field are studied by examining the generalized structure functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…In other words, if we interpret scaling index α A as α A = 2H , we have a transition from a noisy anti-persistent (H < 0.5) signal to a smoother persistent (H > 0.5) one, in agreement with a similar result of Uritsky et al (2006) obtained from the analysis of the roughness exponent of auroral surfaces during substorms. Interestingly, Kozelov and Golovchanskaya (2006) reported a similar variation of the scaling index for auroral luminosity observed during intensification of a transpolar arc under positive IMF B z , that is, in obviously non-substorm conditions.…”
Section: Scaling Behavior Of the Aurora At Substorm Early Expansion Asupporting
confidence: 57%
“…In other words, if we interpret scaling index α A as α A = 2H , we have a transition from a noisy anti-persistent (H < 0.5) signal to a smoother persistent (H > 0.5) one, in agreement with a similar result of Uritsky et al (2006) obtained from the analysis of the roughness exponent of auroral surfaces during substorms. Interestingly, Kozelov and Golovchanskaya (2006) reported a similar variation of the scaling index for auroral luminosity observed during intensification of a transpolar arc under positive IMF B z , that is, in obviously non-substorm conditions.…”
Section: Scaling Behavior Of the Aurora At Substorm Early Expansion Asupporting
confidence: 57%
“…The spatio-temporal technique (Uritsky et al, 2002;Kozelov et al, 2004) gives the uniform scaling features of avalanchelike transients during the substorm expansion phase from scales of a few square kilometers and a few seconds, up to 10 6 square kilometers and a few hours. The analysis of the PDFs and GSFs presented here shows that the features (power-law range of GSF vs. scale, evidence of the intermittence, leptokurtic shape of the PDFs, and collapse of the rescaled PDFs) of spatial auroral fluctuations on scales of 3-20 km are the same as for the non-substorm event discussed in Kozelov and Golovchanskaya (2006). This indicates that the scaling relations may represent more universal signatures of spatio-temporal complex dynamics than those pertaining to substorm-like transients in the magnetospheric plasma.…”
Section: Discussionmentioning
confidence: 85%
“…The relationship between the high‐latitude electric and magnetic turbulence and the Birkeland field‐aligned currents/large‐scale convection velocity shears was evidenced by Golovchanskaya et al [2006]. The turbulent properties of small‐scale electric and magnetic fields at high latitudes have recently been strongly supported by Tam et al [2005], Kozelov and Golovchanskaya [2006], and Golovchanskaya et al [2006]. Those authors demonstrated the power‐law form of the electric and magnetic field spectra, non‐Gaussian character of the probability distribution functions (PDF) of amplitudes, collapse of the re‐scaled PDFs onto a single curve and flatness in excess of 3.…”
Section: Introductionmentioning
confidence: 94%